Highly pathogenic avian H5N8 influenza viruses: should we be concerned?. Issue 1 (1st January 2018) - Tate, M. D.
ABSTRACT: Avian influenza A viruses pose a constant threat to global human health as sporadic infections continue to occur with associated high mortality rates. To date, a number of avian influenza virus subtypes have infected humans, including H5N1, H7N9, H9N2 and H7N7. The majority of 'bird flu' cases are thought to have arisen from direct contact with infected poultry, particularly in live markets in Asia. 1 While human cases of the H5N8 subtype have not been documented as yet, there is the potential that H5N8 viruses could acquire mutations which favour infection of human cells. There is also the possibility that novel viruses with a tropism for human cells could be generated if H5N8 should reassasort with other circulating avian viruses, such as those of the H5N1 subtype. The emergence of a novel H5N8 virus with the capability of infecting humans could have drastic consequences to global health.